Process Management as a Key Factor in The Long-Term Viability of Business Systems - Kremsar, Sara; Kern, Tomaž; Krhač Andrašec, Eva (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
In the modern business environment characterized by rapid technological changes and global competition, business systems need to optimize their operations to ensure long-term viability continuously. The long-term viability of business systems refers to their ability to survive and grow under dynamic market conditions over an extended period. Various internal and external factors can influence this ability. This paper aims to identify the key factors that affect the long-term viability of business systems. Additionally, we aim to determine the importance of process management by positioning it within the list of identified factors. To achieve this, a multidisciplinary SCOPUS database was reviewed. Based on the theoretical review, we compiled a set of key factors contributing to the long-term viability of business systems. The prepared review article can serve as a starting point for further research focused on an in-depth analysis of individual key factors and their interconnections. The identified set also serves as a foundation for developing a model of the most important factors influencing the long-term viability of business systems, which will have practical value for various business systems.